Toward Green Pesantren and Environmental Philanthropy Based on Maqasid al-Sharia - Muhammad Yafi Sabilul Ahkam; Satya Graha Habibilah (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2025)
Abstract: Indonesia’s waste management crisis reflects systemic problems that cannot be adequately addressed through technical solutions alone. Effective responses require governance arrangements that connect public policy, financing, accountability mechanisms, and the sustained cultivation of pro environmental practices at the community level. The growing orientation of Islamic philanthropy toward environmental concerns has created opportunities for philanthropic fund managers to support environmental preservation programs, including the “Green Pesantren” (Pesantren Hijau) initiative led by NU Care LAZISNU within the PBNU network. A qualitative case study design is used to examine program governance in pilot Islamic boarding schools through interviews, participatory observation, and document analysis, followed by thematic analysis. The findings indicate that program effectiveness relies on kiai leadership in shaping norms and discipline, santri participation that develops from procedural involvement toward more autonomous management, and LAZISNU’s technical facilitation focused on capacity building and system strengthening. Program impacts are multidimensional, encompassing behavioural change and improved environmental quality through source-based waste separation and water and energy conservation, the creation of micro scale economic value through Waste Banks and circular economy practices, and stronger social capital through collective action and communal accountability. Read through the maqāṣid al-sharīʿah paradigm, these findings constitute a form of ḥifẓ al-bīʾah that can be assessed through governance mechanisms and the sustainability of the Green Pesantren’s impacts. In this framing, ḥifẓ al-bīʾah is not merely an ethical claim, but an evaluative lens that offers a comparative reference for faith based environmental philanthropy initiatives. Abstrak: Krisis pengelolaan sampah di Indonesia menunjukkan persoalan sistemik yang tidak memadai jika ditangani hanya dengan solusi teknis. Persoalan tersebut menuntut tata kelola yang mampu mempertautkan kebijakan, pembiayaan, mekanisme pertanggungjawaban, serta pembiasaan perilaku pada tingkat komunitas. Pergeseran orientasi filantropi Islam ke isu lingkungan memberi peluang bagi pengelola dana filantropi untuk mendukung program pelestarian lingkungan, termasuk Program Pesantren Hijau yang dipelopori NU-Care LAZISNU bersama jejaring PBNU. Pendekatan kualitatif dengan desain studi kasus digunakan untuk menelaah tata kelola program pada pesantren percontohan melalui wawancara, observasi partisipatif, dan analisis dokumen, kemudian dianalisis secara tematik. Temuan memperlihatkan bahwa efektivitas program bertumpu pada kepemimpinan kiai dalam membentuk norma dan disiplin, partisipasi santri yang berkembang dari keterlibatan prosedural menuju pengelolaan yang lebih mandiri, serta pendampingan teknis LAZISNU yang berfokus pada pembangunan kapasitas dan penataan sistem kerja. Dampak program bersifat multidimensional, meliputi perubahan perilaku dan kualitas lingkungan melalui pemilahan sejak sumber, konservasi air dan energi, pembentukan nilai ekonomi skala mikro melalui Bank Sampah dan praktik ekonomi sirkular, serta penguatan modal sosial melalui kerja kolektif dan akuntabilitas komunal. Pembacaan melalui paradigma maqāṣid asy-syarīʿah menempatkan temuan tersebut sebagai praktik ḥifẓ al-bīʾah yang dapat dinilai melalui mekanisme pengelolaan dan keberlanjutan dampak Program Pesantren Hijau. Ḥifẓ al-bīʾah dalam artikel ini bukan sekadar klaim etik, sehingga dapat menjadi rujukan komparatif bagi inisiatif filantropi lingkungan berbasis institusi keagamaan.